PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT UNTUK MENJADI ENTREPRENEUR PADA MAHASISWA STEBIS PAGAR ALAM - Imam Subhi; Julius Julius; Lidya Medianti; Murlita Murlita (IQTISHADUNA, 2022)
This study aims to examine the effect of entrepreneurship education on students' interest in becoming entrepreneurs, and how much influence entrepreneurship education has on interest in becoming entrepreneurs in STEBIS Pagar Alam students. Observing the above objectives, the desired final result is a numerical conclusion, therefore to obtain accurate data and valid results, the study uses a quantitative approach, with the object of the research population totaling 103 people, while the sample is 43 people taken with non-technical techniques. probability sampling. From the results of the study, it was concluded that there was a significant relationship or influence between entrepreneurship education and interest in becoming an entrepreneur in STEBIS Pagar Alam students, this influence can be seen from the variable interest in becoming an entrepreneur in STEBIS Pagar Alam students of 89.2%. Thus, the better the entrepreneurial education provided, the more it will encourage students' interest to become entrepreneurs or businessmen. Penelitian ini bertujuan untuk mengkaji tentang pengaruh pendidikan kewirausahaan terhadap minat mahasiswa untuk menjadi entrepreneur, dan seberapa besar pengaruh pendidikan kewirausahaan terhadap minat untuk menjadi entrepreneur pada mahasiswa STEBIS Pagar Alam. Mencermati tujuan di atas maka hasil akhir yang diinginkan kesimpulan berupa numerik, oleh karena itu untuk mendapatkan data yang akurat dan hasil yang valid maka penelitian menggunakan pendekatan kuantitatif, dengan obyek populasi penelitian berjumlah 103 orang, adapun yang dijadikan sampel 43 orang yang diambil dengan teknik non propability sampling. Dari hasil kajian maka diperolah kesimpulan terdapat hubungan atau pengaruh yang signifikan antara pendidikan kewirausahaan dengan minat untuk menjadi entrepreneur pada mahasiswa STEBIS Pagar Alam, pengaruh tersebut dapat dilihat dari variabel minat untuk menjadi entrepreneur pada Mahasiswa STEBIS Pagar Alam sebesar 89,2%. Dengan demikian maka semakin baik pendidikan interpreneur yang diberikan makan akan semakin mendorong minat mahasiswa untuk menjadi interpreneur atau pebisnis.